História natural de Notodiaptomus amazonicus (Wright, 1935) em lago de área urbana protegida no lavrado de Roraima (Copepoda: Calanoida: Diaptomidae) - Geraldes Primeiro, Luis José de Oliveira (Instituto Nacional de Pesquisas da Amazônia - INPA, 2020)
The study addresses to the copepods natural history of an urban lake in a protected municipal area in the lavrado of Roraima, whose lake has the characteristic of being the unique remnant of urban lakes in Boa Vista. The lake has a round format, measuring near 60 meters in diameter. The research was related to the population structure of the copepodes of the lake. The samples were taken in six visits during December 2014, the dry period of the region, covering three microhabitats: margin with vegetation of gramineans and cyperaceans, limnetical portion and margin with absent vegetation. Each visit corresponded to a sample in one microhabitat – in all 6 samples per microhabitat. These samples also encompassed three phases of the lake – full waters, empting and critical levels of the water. Four questions guided the study concerning the proportions of adults (male and female), copepodits (juveniles) and náuplius (larvae) inside and between the microhabitats. Each question had its respective hypothesis, considered the provisory answer to the question, which results allowed some inferences on the dynamics of the studied copepod population. The main results related to these four questions were: First – i) the proportion of adults and copepodits were greater than the náuplius in the thre microhabitats, ii) the proportion of náuplius, copepodits and adults were greater in the limnetical portion, iii) the proportion of adults was fewer in the margins with vegetation. Second – i) the sexual ratio was 1:1 among the three microhabitats, ii) inside the three microhabitats the proportion between males and females was also 1:1. Third – in the three microhabitats the proportion of females carrying eggs was slightly greater when the lake was full or empting, ii) female carrying eggs was equally distributed in the three microhabitats when the lake was full, iii) the proportion of females carrying eggs was greater in the center and in the margin without vegetation when the lake was in its critical water level. Fourth – i) among the three phases of the lake – full, emptying and critical levels of the water – the copepodits and males and females adults were more abundant than náuplius, ii) the proportion of náuplius was homogenous and more abundant in the high levels of water (full and emptying), less abundant in the critical levels of water, iii) the copepodits were more abundant when the lake was emptying, but homogenous in the extreme phases– full and critical levels, iv) adult males and females had its abundance reduced at the same proportion as the water was decreasing in a sequence of full water, empting and critical levels of water.